Un solo mundo : los hombres en la caverna, liberación y ascensión. (2014)
In this paper the author approaches the complex relationship between the three similes employed by Plato en The Republic, in Books VI and VII. The proposal is that the simile of the cave can be understood as a “phenomenological” movement, that is, a movement from the field of doxa to the noetic field, describing a change of the view if the philosopher about the ens. Thus a modification is set ti the traditional interpretation of the simile which presupposes that the cave involves a form of a spatial movement.